Sensitive EDTA-based microbiological assays for detection of metallo-beta-lactamases in nonfermentative gram-negative bacteria - Marchiaro, Patricia (2005)
Fil: Marchiaro, Patricia. Universidad Nacional de Rosario. Departamento de Microbiología; Argentina.